A highly adaptive magnetorheological fluid robotic leg for efficient terrestrial locomotion. (9th August 2016) - Jiang, Nan; Sun, Shuaishuai; Ouyang, Yiming; Xu, Min; Li, Weihua; Zhang, Shiwu
Abstract: To survive in nature, animals adjust the characteristics of their legs or fins to adapt the motion to their environment. Inspired by the locomotion of animals, a study on the tunable stiffness and damping of a leg will help in the development of intelligent locomotion robots. In this paper we report on the development and experiment of a novel and simple robotic leg that can be adapted to the environment via a smart magnetorheological fluid (MRF). The robotic leg consists of a rotation MRF damper, a torsional spring, a 'foot' and a 'leg'. The curved part of the 'foot' makes contact with the grounds while the other end is linked to an outer cylinder of the MRF damper with an inelastic cable. The variable force arm rising from the MRF damper and the torsional spring can help the leg adapt to a changing environment. The characteristics of the MRF damper have been investigated and a model is built to describe its mechanical features when different currents are applied to the MRF damper. A test on a linear dynamic test instrument has been conducted to verify the accuracy of the model. The robotic leg is installed in a locomotion platform to investigate the speed of its locomotion and the cost of the transport; the result demonstrated the feasibility and adaptability of the leg when walking on hard terrain. Its simple structure, high adaptability, and easy control of the MRF leg helped in the design and development of a high performance field robot that can adapt to various environments.